Small amounts of ammonium (NH _4^+ ) can increase growth of maize (Zea mays). Issue 6 (16th September 2016) - George, Jessey; Holtham, Luke; Sabermanesh, Kasra; Heuer, Sigrid; Tester, Mark; Plett, Darren; Garnett, Trevor
Abstract: Nitrate (NO _3^ - ) and ammonium (NH _4^+ ) are the predominant forms of nitrogen (N) available to plants in agricultural soils. Nitrate concentrations are generally ten times higher than those of NH _4^+ and this ratio is consistent across a wide range of soil types. The possible contribution of these small concentrations of NH _4^+ to the overall N budget of crop plants is often overlooked. In this study the importance of this for the growth and nitrogen budget of maize ( Zea mays L.) was investigated, using agriculturally relevant concentrations of NH _4^+ . Maize inbred line B73 was grown hydroponically for 30 d at low (0.5 mM) and sufficient (2.5 mM) levels of NO _3^ - . Ammonium was added at 0.05 mM and 0.25 mM to both levels of NO _3^ - . At low NO _3^ - levels, addition of NH _4^+ was found to improve the growth of maize plants. This increased plant growth was accompanied by an increase in total N uptake, as well as total phosphorus, sulphur and other micronutrients in the shoot. Ammonium influx was higher than NO _3^ - influx for all the plants and decreased as the total N in the nutrient medium increased. This study shows that agriculturally relevant proportions of NH _4^+ supplied in addition to NO _3^ - can increase growth of maize.